Report Risk of Malignancy Index of Ovarian Cancer Patients in Dr. Sardjito Hospital, Yogyakarta - Rachmasari Putri, Henny Meitri Andrie (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: To analyse retrospectively the score of the risk of malignancy index (RMI) in determining malignancy in the patients with ovarian mass in Dr. Sardjito Hospital Yogyakarta. Method: Retrospective analysis. Results: Ninety patients with complete medical record and adnexal mass were enrolled in the study from January 2007 to March 2009. Subjects consisted of 70 patients (77.78%) diagnosed with malignant ovarian mass and 20 patients with benign mass (22.22%), More than half of the malignant ovarian mass were serous carcinomas and at advanced stages (51.43% and 51.43% subsequently). Univariate analysis presented significant difference for ultrasound score and serum Ca-125 level in identification of ovarian malignancy, but not with the age or the menopausal status. The performance of RMI (â¥ 200 for malignancy) had a sensitivity of 70%, a specificity of 75%, a positive predictive value of 90.74%, and negative predictive value of 41.67%. The serum Ca-125 level had a sensitivity of 81.43%, a specificity of 60%, a positive predictive value of 87.69%, and a negative predictive value of 48%. The ultrasound score had a sensitivity of 65.71%, a specificity of 65%, a positive predictive value of 86.79%, and a negative predictive value of 35.14%. Conclusion: Due to the nature of retrospective study, RMI is reliable for identification of malignant and benign ovarian mass improve the management of ovarian mass including referral system and the decision regarding the approach used during surgery. [Indones J Obstet Gynecol 2010; 34-3: 131-5] Keywords: risk of malignancy index, RMI, ovarian cancer, ovarian malignancies, ovarian carcinomas